PENGARUH MODEL PEMBELAJARAN YURISPRUDENSI UNTUK MENINGKATKAN PEMAHAMAN KONSEP (Studi Eksperimen Dalam Pembelajaran IPS di Kelas V MI) - Tusriyanto, Tusriyanto, (JURNAL TAPIS, 2012)
AbstractLearning conditions IPS is still found weaknesses in the field include the following (1) conventional learning models (2) studens are only used as a learning object, in connection with this, the need for chanes in the application of learning models that involve more studens in the learning prosess, so students can grasp the concept. With direct involvement in the learning process students can grasp the concept. One model of learning is a model of jurisprudence, this instructional model emphasizes that in any learning process students are active in constructing their own knowlage (student centered). The study was conducted to determine how much influence the jurisprudennce learning model in theaching socialstudies to enhance studentâs understanding of concepts. This study uses quasi experiment conduced on students of class v MI tatalinh 60 students, the class consists of 30 students and a control expermen 30 students, at MIN 01 and MIN 02. Data were collected trough a written test (pretest and posttest) and observation. Data processing learning outcame were analyzed using SPSS version 12, the normality test, hogenity test and t-test. Based on the data obtained and the results of pretest and postes data analysys above has beenproven that students who gain learning with the learning model jurisprudential concept comprehension was significantly increased when compared with studend who received conventional learning.Keywords: Influence, jurisprudence learning models, understanding of the concept.